Cheat software – 'doping' in online games. (December 2019) - Lober, Andreas; Conraths, Timo
Abstract : This article considers the legal issues surrounding the use of cheat software in online games, especially with reference to those games featuring significant online multiplayer functionality, such as massively multiplayer online games. Given the propensity of cheat software to ruin the gaming experience of bona fide players in such multiplayer settings, potentially resulting in significant economic and reputational losses for game publishers, the article evaluates the methods which may be employed by the game publisher to restrict the development, distribution and use of cheat software by the latter's developers, publishers and users. Using provisions of trademark, copyright and competition law, the authors examine the tools available to game publishers to stifle the spread of cheat software and maintain a fair playing field within their online multiplayer games.